Development and preliminary performance evaluation of a solar collector for adsorption refrigerator (2009)
The design and construction of a flat plate solar collector is presented in this paper. The solar collector was designed to power adsorption refrigerator using activated carbon/methanol pair. Design was such as to provide simplicity and yet ruggedness for harsh operating environment in the tropical climate of Nigeria. For methanol desorption, the collector must reach a maximum temperature of at least 100°C. Performance results showed that the maximum temperature of 108°C attained in the solar collector was adequate for methanol generation, while maximum received insolation of 1000 kW/m2 was sufficient for methanol desorption.